Computers : the user perspective. - Hutchinson, Sarah E. (Richard D. Irwin, Inc., 1990)
"We believe that our book offers many of the features desired by today's instructors of the introductory course. We wrote our book to provide instructors and students with: A User Orientation Our book is directly relevant to the user. It prepares students to use microcomputers in business and to communicate effectively with computer specialists such as programmers. Everything in this book - every topic, illustration, case, and so on - is geared to the user, providing what he or she needs to know to prepare for a business career. For example, in Chapter 9, "Systems Development Life Cycle," we explain the phases of the cycle so that students can see where they"ll be involved in the process as users and thus be better able to communicate with the analysts and programmers to get their needs met. If the user doesn't need to know something, it's not in this book." (Copied from preface).